2021
DOI: 10.31195/ejejfs.1001338
|View full text |Cite
|
Sign up to set email alerts
|

Pollen analysis of honeys from Yığılca region (Düzce), Turkey

Abstract: The aim of this study is to determine the plant species preferred by Apis mellifera L., which is a valuable genotype in terms of vitality and high honey production. For this purpose, seven honey samples from Yığılca region in Düzce (Turkey) were examined for pollen analysis. As a result of the pollen analysis on these samples, it was determined that Yığılca local honeybee use pollen grains of 43 different taxa from 26 families. Six samples of honey were unifloral (> 45% pollen of one taxon in sample) with four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…In another study examining the honey from the Düzce Yığılca region, pollen detection of 43 different taxa from 26 families was conducted. In two of the seven samples, C. sativa pollen was recorded dominantly with percentages of 91.5% and 92.5% [20]. Another palynological study conducted in the Yığılca region examined chestnut honey propolis, and identified C. sativa pollen at a rate of 80.5% [26].…”
Section: (A) (B)mentioning
confidence: 89%
“…In another study examining the honey from the Düzce Yığılca region, pollen detection of 43 different taxa from 26 families was conducted. In two of the seven samples, C. sativa pollen was recorded dominantly with percentages of 91.5% and 92.5% [20]. Another palynological study conducted in the Yığılca region examined chestnut honey propolis, and identified C. sativa pollen at a rate of 80.5% [26].…”
Section: (A) (B)mentioning
confidence: 89%
“…2019;Sabo et al, 2011;Yildirim et al, 2021).Morfologická charakteristika peľu: Pri hodnotení peľových zŕn gaštana jedlého sme zistili dĺžku polárnej osi v rozpätí 13,52 -22,94 µm a dĺžku ekvatoriálnej osi (priemer peľových zŕn) 6,64 -10,54 µm (tab. 11).…”
unclassified